2007
DOI: 10.1542/peds.2007-2638
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Medical Home in Family-Centered Early Intervention Services

Abstract: There is growing evidence that early intervention services have a positive influence on the developmental outcome of children with established disabilities as well as those who are considered to be "at risk" of disabilities. Various federal and state laws now mandate the establishment of community-based, coordinated, multidisciplinary, family-centered programs that are accessible to children and families. The medical home, in close collaboration with the family and the early intervention team, can play a criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Some studies indicate that children with an identified at-risk condition or a clinical diagnosis have an earlier age of first concern from parents or caregivers, an earlier development of an Individual Family Service Program, and an earlier receipt of early intervention services [7477]. Other studies indicate that children with risk factors for cognitive deficits are more likely to be screened for developmental delays and that screened children are more likely to be referred for and receive early intervention services [76,78].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies indicate that children with an identified at-risk condition or a clinical diagnosis have an earlier age of first concern from parents or caregivers, an earlier development of an Individual Family Service Program, and an earlier receipt of early intervention services [7477]. Other studies indicate that children with risk factors for cognitive deficits are more likely to be screened for developmental delays and that screened children are more likely to be referred for and receive early intervention services [76,78].…”
Section: Resultsmentioning
confidence: 99%
“…10 While EI referrals and enrollment depend on state eligibility criteria, 11 many eligible children are not efficiently connected to services. 12-14 Families of poor 11 and minority children 13-15 may have more trouble accessing services and may be less satisfied when they do receive services.…”
Section: Introductionmentioning
confidence: 99%
“…EI functions include identification (eg, screening and referral), diagnosis, service coordination, and direct interventions. Both the Institute of Medicine10 and the American Academy of Pediatrics11 support use of comprehensive follow-up and EI services for premature infants. Additionally, EI enrollment for ELBW children during the first year of life has been shown to be positively associated with receipt of a needed follow-up ophthalmologic examination 12…”
mentioning
confidence: 99%